Learning together program for reading and writing interest in Arahan Kidul Village - Eka Rahmawati; Syamsul Hadi Senen (Universitas Pendidikan Indonesia, 2023)
Reading and writing literacy is the main ability that students must master, because reading and writing can greatly impact the quality of human life. Arahan sub-district, Arahan Kidul village is one of the places where the Indonesian Education University's Thematic Real Work Lecture (KKN-T) program is held for one month. It is known that there is still little attention paid to interest in reading and writing in the Arahan Village, therefore, in KKN-T activities, there is a joint learning work program which is expected to help students to be more active in learning to read and write. In this article, we will discuss the initial stages of activities and the implementation stages of the joint learning program. This article uses a descriptive method with a qualitative approach by collecting data obtained from observations and short interviews with students. The results found from this research were that students' lack of interest in reading and writing was due to a lack of supporting facilities and infrastructure. Meanwhile, students' motivation to learn to read and write is classified as very high. The impact resulting from this KKN-T activity is that human resources are facilitated to help guide students in learning to read and write so that students' enthusiasm is awakened to be more active in learning to read and write independently. Future recommendations hope the village and school can provide innovation and special learning media for elementary school students in Arahan Kidul. Abstrak Literasi baca-tulis merupakan kemampuan utama yang wajib dikuasi oleh siswa, karena baca-tulis dapat memberikan dampak yang besar bagi kualitas kehidupan manusia. Kecamatan Arahan desa Arahan Kidul merupakan salah satu tempat dilaksanakannya program Kuliah Kerja Nyata Tematik (KKN-T) Universitas Pendidikan Indonesia yang berlangsung selama 1 bulan. Diketahui bahwasannya minat baca-tulis di desa arahan masih kurang diperhatikan oleh karena itu, dalam kegiatan KKN-T terdapat program kerja belajar bersama yang diharapkan dapat membantu siswa untuk lebih giat belajar baca-tulis. Dalam artikel ini akan membahas terkait tahap awal kegiatan dan tahap pelaksanaan dari program belajar bersama. Artikel ini menggunakan metode deskriptif dengan pendekatan kualitatif dengan pengumpulan data yang diperoleh dari hasil observasi serta wawancara singkat dengan siswa. Hasil yang ditemukan dari penelitian ini adalah kurangnya minat baca-tulis siswa dikarenakan kurangnya sarana dan prasarana serta fasilitas yang mendukung. Sedangkan, motivasi belajar baca-tulis siswa tergolong sangat tinggi. Dampak yang dihasilkan dari kegiatan KKN-T ini adalah terfasilitasinya SDM yang membantu dalam membimbing siswa belajar membaca dan menulis sehingga terbangunya semangat siswa untuk lebih giat belajar membaca dan menulis secara mandiri. Rekomendasi kedepannya semoga pihak desa maupun sekolah mampu memberikan inovasi serta media belajar khusus bagi siswa-siswi sekolah dasar di Arahan Kidul. Kata Kunci: Baca-tulis; belajar bersama; literasi; pendidikan